Assessment of Diverse Solid−State Accelerated Autoxidation Methods for Droperidol - Jayant Iyer; Isha Saraf; Andrew Ray; Michael Brunsteiner; Amrit Paudel (MDPI AG, 2022)
The present study aimed to investigate methods for accelerating autoxidation of crystalline drugs in the solid-state that can potentially predict real−time stability. Solid droperidol (DPD) was selected as the model drug. A common free−radical initiator, 2,2'−azobisisobutyronitrile (AIBN), was used to induce autoxidation in solutions. AIBN decomposes at elevated temperatures to yield carbon−centred cyano−isopropyl free radicals that can auto−oxidize neighboring drug molecules. Although the reaction of AIBN is relatively straightforward in solution, it is less so in solids. In this study, we used solid AIBN mixed with DPD powder in the presence and absence of pressurized oxygen headspace. Samples were prepared directly in the form of binary mixtures with DPD and additionally in the form of powder compact/pellet with DPD. The main challenge in carrying out the reaction was related to the preservation of AIBN at elevated temperatures due to the disintegration of the pellet containing the latter. A commercially available free−radical coated silica particle (i.e., 2,2,6,6−tetramethyl−1−piperinyloxy (TEMPO) or (SiliaCATTM TEMPO)) was tested as a potential stressor, but with limited success to induce autoxidation. The most valuable results were obtained when a physical mixture of pre−milled PVP K−60 containing free radicals and DPD was exposed to elevated oxygen−temperature conditions, which yielded significant degradation of DPD. The study highlights the practical challenges for conducting accelerated solid−state stress studies to assess the autoxidation susceptibility of drugs using traditional free−radical initiators and presents a proof of application of milled PVP with free−radical as a potential alternative.